2017
DOI: 10.7202/1043129ar
|View full text |Cite
|
Sign up to set email alerts
|

Entrainer la cognition sociale auprès d’enfants présentant une déficience intellectuelle

Abstract: Cette étude investigue la possibilité de modifier les compétences socio-émotionnelles d’enfants présentant une déficience intellectuelle (DI) grâce à un entrainement de la Théorie de l’esprit (ToM) ou du Traitement de l’information sociale (TIS). Dix-huit enfants présentant une DI sont répartis aléatoirement dans le groupe contrôle ou dans un des deux groupes expérimentaux, entrainant grâce à une séance, soit la ToM, soit le TIS. Avant et après ceux-ci, une évaluation de l’âge développemental, des compétences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…As demonstrated by other studies (e.g. Jacobs et al, 2016;Lachavanne & Barisnikov, 2013;Stewart & Singh, 1995), an adapted training focusing on affective ToM supports the understanding of desires and emotions (notably the causes of emotions) despite the inter-and intra-variability among children. In fact, some children in the present sample displayed different levels of intensity and progression, which influences the improvement of ToM abilities in various ways.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As demonstrated by other studies (e.g. Jacobs et al, 2016;Lachavanne & Barisnikov, 2013;Stewart & Singh, 1995), an adapted training focusing on affective ToM supports the understanding of desires and emotions (notably the causes of emotions) despite the inter-and intra-variability among children. In fact, some children in the present sample displayed different levels of intensity and progression, which influences the improvement of ToM abilities in various ways.…”
Section: Discussionsupporting
confidence: 66%
“…Shure, 1993;Webster-Stratton & Hammond, 1997), or (3) IDs (e.g. Jacobs, Léonard, Nader-Grosbois, Houssa, & Mazzone, 2016;Lachavanne & Barisnikov, 2013;Stewart & Singh, 1995). Several issues emerged from these studies among samples of participants with IDs or autism spectrum disorders (see appendixes A and B).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that different programs improve the socio-emotional competences of these children (e.g. Adibsereshki, Abdolahzadeh, Karmilo, & Hasanzadeh, 2014;Jacobs, Léonard, Nader-Grosbois, Houssa, & Mazzone, 2016). Furthermore, as mentioned above and as suggested by Green and Baker (2011), children with ID would certainly benefit from exaggeration or emphasis when their parents converse, express emotions or react supportively to their children.…”
Section: Discussionmentioning
confidence: 86%
“…However, only a very few of these have related to subjects displaying IDs (e.g. Jacobs, Léonard, Nader-Grosbois, Houssa, & Mazzone, 2016;Jacobs & Nader-Grosbois, 2020a;Lachavanne & Barisnikov, 2013;Stewart & Singh, 1995). These experimental studies indicate the effectiveness of ToM interventions among populations with IDs depending on the subjects' characteristics, the intervention targets and the timing, as well as on the use of specific evaluation measures, materials and techniques (for a review see Jacobs & Nader-Grosbois, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…These experimental studies indicate the effectiveness of ToM interventions among populations with IDs depending on the subjects' characteristics, the intervention targets and the timing, as well as on the use of specific evaluation measures, materials and techniques (for a review see Jacobs & Nader-Grosbois, 2020a). After participating in ToM training, elementary school children with IDs show an improved understanding of affective mental states (as emotions and desires; Jacobs et al, 2016;Jacobs & Nader-Grosbois, 2020a; Lachavanne & Barisnikov, 2013;Stewart & Singh, 1995) and also of cognitive mental states (e.g. belief, false beliefs, perspective taking, intentions or pretense; Jacobs et al, 2016; Jacobs & Nader-Grosbois, 2020a; Montoya-Rodríguez & Molina-Cobos, 2019).…”
Section: Introductionmentioning
confidence: 99%